Parasite Genomics Protocols - Peacock, Christopher.; Peacock, Christopher. (Methods in Molecular Biology,, 2015)
Parasite Genomics Protocols, Second Edition expands upon the previous edition with current, detailed methodologies that have been adapted to research parasites in the post genomic era.  With new chapters on parasite studies, helminth pathogens, and protocols for undertaking other large-scale ‘omics’ methodologies. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.  Authoritative and practical, Parasite Genomics Protocols, Second Edition offers a wide-ranging collection of diverse methods and protocols for further study into these unique organisms.